Fully synthetic Tn-based three-component cancer vaccine using covalently linked TLR4 ligand MPLA and iNKT cell agonist KRN-7000 as built-in adjuvant effectively protects mice from tumor development - Deying Yang; Xiang Luo; Qinghai Lian; Lingqiang Gao; Chengxin Wang; Xiaoxiao Qi; Rong Zhang; Zhongqiu Liu; Guochao Liao (Acta Pharmaceutica Sinica B, 2022)
We present a new strategy for self-adjuvanting vaccine development that has different types of covalently-linked immunostimulants as the carrier molecule. Using Tn antigen as the model, a three-component vaccine (MPLA-Tn-KRN7000) containing the TLR4 ligand MPLA and the iNKT cell agonist KRN7000 was designed and synthesized. This expands fully synthetic self-adjuvanting vaccine studies that use a single carrier to one with two different types of carriers. The corresponding two-component conjugate vaccines Tn-MPLA, Tn-KRN7000 and Tn-CRM197 were also synthesized, as controls. The immunological evaluation found that MPLA-Tn-KRN7000 elicits robust Tn-specific and T cell-dependent immunity. The antibodies specifically recognized, bound to and exhibited complement-dependent cytotoxicity against Tn-positive cancer cells. In addition, MPLA-Tn-KRN7000 increased the survival rate and survival time of tumor-challenged mice, and surviving mice reject further tumor attacks without any additional treatment. Compared to the glycoprotein vaccine Tn-CRM197, the two-component conjugate vaccines, Tn-MPLA and Tn-KRN7000, and the physical mixture of Tn-MPLA and Tn-KRN7000, MPLA-Tn-KRN7000 showed the most effect at combating tumor cells both in vitro and in vivo. The comparison of immunological studies in wild-type and TLR4 knockout mice, along with the test of binding affinity to CD1d protein suggests that the covalently linked MPLA-KRN7000 immunostimulant induces a synergistic activation of TLR4 and iNKT cell that improves the immunogenicity of Tn. This work demonstrates that MPLA-Tn-KRN7000 has the potential to be a vaccine candidate and provides a new direction for fully synthetic vaccine design.